Experiments with Body Agent Architecture The 586-year-old Spiritello in Il Regno Digitale - Ayuso, Alessandro (Design Research in Architecture, 2022)
Experiments with Body Agent Architecture puts forward the notion of body agents: non-ideal, animate and highly specific figures integrated with design to enact particular notions of embodied subjectivity in architecture. Body agents present opportunities for architects to increase imaginative and empathic qualities in their designs, particularly amidst a posthuman condition. Beginning with narrative writing from the viewpoint of a body agent, an estranged 'quattrocento spiritello' who finds himself uncomfortably inhabiting a digital milieu (or, as the spiritello calls it, 'Il Regno Digitale'), the book combines speculative historical fiction and original design experiments. It focuses on the process of creating the multi-media design experiments, moving from the design of the body itself as an original prosthetic to architectural proposals emanating from the body. A fragmented history of the figure in architecture is charted and woven into the designs, with chapters examining Michelangelo's enigmatic figures in his drawings for the New Sacristy in the early sixteenth century, Gian Lorenzo Bernini's physically ephemeral 'putti' adorning chapels and churches in the seventeenth century, and Austrian artist-architect Walter Pichler's personal and prescient figures of the twentieth century.